Lexical frequency effects on articulation: a comparison of picture naming and reading aloud - Mousikou, Petroula; Rastle, Kathleen (Frontiers in Psychology, 2015)
The present study investigated whether lexical frequency, a variable that is known to affect the time taken to utter a verbal response, may also influence articulation. Pairs of words that differed in terms of their relative frequency, but were matched on their onset, vowel, and number of phonemes (e.g. map vs. mat, where the former is more frequent than the latter) were used in a picture naming and a reading aloud task. Low-frequency items yielded slower response latencies than high-frequency items in both tasks, with the frequency effect being significantly larger in picture naming compared to reading aloud. Also, initial-phoneme durations were longer for low-frequency items than for high-frequency items. The frequency effect on initial-phoneme durations was slightly more prominent in picture naming than in reading aloud, yet its size was very small, thus preventing us from concluding that lexical frequency exerts an influence on articulation. Additionally, initial-phoneme and whole-word durations were significantly longer in reading aloud compared to picture naming. We discuss our findings in the context of current theories of reading aloud and speech production, and the approaches they adopt in relation to the nature of information flow (staged vs. cascaded) between cognitive and articulatory levels of processing.